The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jen.12610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of attractants and traps for monitoring small banded pine weevil Pissodes castaneus

Abstract: This study aimed to develop a semiochemical‐baited trapping system to monitor the populations of small banded pine weevil, Pissodes castaneus, a serious pest in Pinus sylvestris young stands that are weakened by biotic and abiotic factors. The scope of the work included the development of a dispenser for compounds (ethanol and α‐pinene) emitted by P. sylvestris and the pheromones of P. castaneus: grandisol and grandisal. Additionally, the effectiveness of beetle catches in different types of traps (unitrap, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…pitfall traps baited with fresh pine billets > ethanol-and turpentine-baited flight traps > ethanol-and turpentine-baited pitfall traps. Skrzecz et al (2019) found that pheromone-baited unitraps (Figure 9) were particularly efficient for trapping P. castaneus in Poland, catching several hundreds of beetles.…”
Section: Trappingmentioning
confidence: 99%
See 2 more Smart Citations
“…pitfall traps baited with fresh pine billets > ethanol-and turpentine-baited flight traps > ethanol-and turpentine-baited pitfall traps. Skrzecz et al (2019) found that pheromone-baited unitraps (Figure 9) were particularly efficient for trapping P. castaneus in Poland, catching several hundreds of beetles.…”
Section: Trappingmentioning
confidence: 99%
“…Although both P. nemorensis and P. strobi produce the two components, only P. nemorensis has been demonstrated to respond to them in the field, although both species display electrophysiological responses to the semiochemicals (Hibbard and Webster, 1993). Grandisol and grandisal have also been identified in the European species, P. castaneus (Marques et al, 2011), and a combination of both semiochemicals has proven very efficient at trapping this species in Poland (Skrzecz et al 2019), although commercial products are not yet available. Furthermore, pheromones have not been identified for all Pissodes species (https://www.pherobase.com/).…”
Section: Trappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring of Scolytinae with pheromone-baited traps (Galko et al, 2016) or ethanol (Oliveira et al, 2017;Skrzecz et al, 2019) determines population density to assist in the integrated management of these forest pests (Carvalho and Trevisan, 2015;Borkowski, 2017). The fermentation of extractives from newly cut wood forms this compound (Lemos et al, 2020;González-Peñas et al, 2020) indicating plants suitable for colonization by Scolytinae and, therefore, used in traps to attract these beetles (Klingeman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The banded pine weevil, Pissodes castaneus (Coleoptera: Curculionidae), was first detected in Patagonia Argentina in 2005. Along its Eurasian natural distribution it is usually associated with Pinus sylvestris , P. pinaster and other European pine species (Skrzecz et al, 2019). However, this weevil has been able to invade different geographic areas in Latin America and successfully colonize several American pine species.…”
Section: Introductionmentioning
confidence: 99%